The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1080/10548408.2017.1363684
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating museum visitor experiences based on user-generated travel photos

Abstract: This research introduces online travel photos published on social media platforms as a complementary data resource to examine the behavior and experience of museum visitors. The practical value of online travel photos is demonstrated through a case study of popular Hong Kong museums, particularly by using the photo content and metadata available from the Flickr platform. The proposed approach is a generic method for understanding museum visitor behavior and preferences, and supports museum practitioners in dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 41 publications
1
15
0
4
Order By: Relevance
“…Wall (2015) found that 89% of the 22,000 photos about The Metropolitan Museum of Art posted on Flickr included an artwork. Vu et al (2018) also used Flickr to examine visitor experiences based on travel photos and they also determined that visitors were more interested in artifacts, as well as indoor scenes. In another study, this time examining Twitter, the main subject depicted by visitors at The Tanks at Tate Modern was the museum space, due to the uniqueness of it, but then closely followed by the live and performance art presented (Villaespesa, 2013).…”
Section: Context: Evolution Of Social Media At the Museummentioning
confidence: 99%
“…Wall (2015) found that 89% of the 22,000 photos about The Metropolitan Museum of Art posted on Flickr included an artwork. Vu et al (2018) also used Flickr to examine visitor experiences based on travel photos and they also determined that visitors were more interested in artifacts, as well as indoor scenes. In another study, this time examining Twitter, the main subject depicted by visitors at The Tanks at Tate Modern was the museum space, due to the uniqueness of it, but then closely followed by the live and performance art presented (Villaespesa, 2013).…”
Section: Context: Evolution Of Social Media At the Museummentioning
confidence: 99%
“…Further, as catalogued forms of heterogeneous consumer experiences, services marketers would be able to pinpoint attributes of perceived value through IWOM that are instrumental in designing strong brand experiences and improving on aspects of services operations (Brady et al, 2008;Field et al, 2017). As an illustration, museum operators could use IWOM to understand consumer preferences and use of exhibition space (Vu et al, 2018).…”
Section: Implications To Practicementioning
confidence: 99%
“…They pointed to linkages between tourists' experience and satisfaction with the cultural elements that were associated with the services provided. Indeed, when the behaviour of museum visitors and their experiences were understood, tourist's attraction to specific tourism destinations would be enhanced (Vu et al, 2018). Previous literature indicates that many museums customers consider satisfaction as a critical factor in the discussions on museum experience (Harrison and Shaw, 2004).…”
Section: Museum Experience and Satisfactionmentioning
confidence: 99%